Study of tribovoltaic effect when Cu electrode sliding on silicon electrodes - Jin, Zhuolin (Nanyang Technological University, 2022)
The demand for sustainable power supplies to power a large number of electronics is becoming increasingly significant with the rapid development of Internet of Things. Harvesting energy from nature such as tidal energy, wind energy and human mechanical energy is regarded as a solution to meet the demand for power supplies. The triboelectric generators have attracted numerous attentions recently for the reason that it provides another technique that can convert mechanical energy to electric energy. For the purpose of well apply to portable electronics, different types of electric generators developed from the triboelectric generators have been carried out. In this project, a tribovoltaic device with a metal probe sliding against doped semiconductors or solar cells which can generate direct current is studied. For the n-type silicon, the generated DC current flowed in the same direction with the built-in electric field between copper and the electrodes. For the p-type silicon, the generated DC current flowed in the opposite direction with the built-in electric field. The generated short-circuit currents from these electrodes were increased with the contact force. For the solar cell, the generated current did not depend on the contact force between the copper probe and solar cell, but the current flow direction was dependent on the Cu probe sliding directions.